DEVELOPING STUDENT CREATIVITY AS A PSYCHOLOGICAL-PEDAGOGICAL PROBLEM - O.I.Tolipova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article identifies effective ways to prepare future teachers for creative activity in higher education institutions and selects its specific content, as well as a clear way to generalize the creativity, social and professional training of future professionals in the educational process and tools are shown